Bridging the Silence: Teachers’ Lived Experiences of Teaching Reading to Struggling Learners - Rejean Nogot; Juanita Corre (International Journal on Integrated Education, 2026)
This study explores the lived experiences of Grade 1-3 teachers of teaching reading to struggling learners at Pulong Sta. Cruz Elementary School, a public elementary school in Santa Rosa City, Laguna. This aims to understand how teachers perceive and respond to the challenges and needs of struggling learners in their daily teaching practice. Using phenomenological design under qualitative approach, the study gathered data through in-depth interviews with ten Grade 1-3 teachers using semi-structured interview guide. Interviews focused on teachers’ daily practices, challenges, emotional responses, and strategies when teaching reading among struggling learners. Data were analyzed thematically to identify recurring patterns and meaningful experiences. Findings revealed that teachers experience responsibility and emotional strain while "bridging the silence" of struggling learners through informal assessments, repetition, one-on-one support, and peer activities despite lacking formal programs. Four key insights emerge: teacher agency (relational warmth + structured pedagogy) drives literacy success; multidimensional reading difficulties demand integrated assessment, multisensory engagement, and emotional support; consistent 10-minute daily drills outperform sporadic high-intensity sessions for fluency/memory retention; and centralized resources like Teacher's Guidebook with Marungko drills and localized scaffolding reduce strain while enabling evidence-based remediation.